2001
DOI: 10.1080/152873901750128326
|View full text |Cite
|
Sign up to set email alerts
|

Intake Of Dioxins and Related Compounds from Food in the U.S. Population

Abstract: The first U.S. nationwide food sampling with measurement of dioxins, dibenzofurans, and coplanar, mono-ortho and di-ortho

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
115
1
4

Year Published

2004
2004
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 207 publications
(122 citation statements)
references
References 29 publications
2
115
1
4
Order By: Relevance
“…The daily dioxin intake (DDI) was estimated as per previous publications by assuming that the infant (0-24 weeks) consumes 800 ml of milk per day (Schecter et al 2001, Tai et al 2011) and taking the weight of the infant at the time into account. The intake value was calculated using the following equation: DDI = 800 × (% fat content of milk/100) × (PCDD/PCDF TEQ in breast milk in pg/g lipid)/(kg of infant weight).…”
Section: Estimation Of the Daily Dioxin Intake Of Infants From Breastmentioning
confidence: 99%
“…The daily dioxin intake (DDI) was estimated as per previous publications by assuming that the infant (0-24 weeks) consumes 800 ml of milk per day (Schecter et al 2001, Tai et al 2011) and taking the weight of the infant at the time into account. The intake value was calculated using the following equation: DDI = 800 × (% fat content of milk/100) × (PCDD/PCDF TEQ in breast milk in pg/g lipid)/(kg of infant weight).…”
Section: Estimation Of the Daily Dioxin Intake Of Infants From Breastmentioning
confidence: 99%
“…Because on their fat-seeking nature, they can bioaccumulate throughout the food chain, finally reaching humans. The major route of human exposure to dioxins and furans is through the consumption of food (490%) such as milk, dairy products, fish, meat, and eggs (Schecter et al, 2001). Current background exposure to dioxins results in a daily uptake of approximately 1-3 pg TEQ (toxicity equivalents)/kg body wt.…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, incidences of contamination of animal products (chickens, eggs, some pigs and cattle, and dairy products) with BCB-and dibenzofuran (Schecter et al, 2001) were reported in Europe and USA. The mechanism of dioxin toxicity is not clear.…”
Section: Application Of Proteomics In Animal and Feed Sciencesmentioning
confidence: 99%